The shining [compact disc, unabridged] - King, Stephen, 1947- (Simon & Schuster Audio, 2005)
This tale of a troubled man hired to care for a remote mountain resort over the winter, his loyal wife, and their uniquely gifted son slowly but steadily unfolds as secrets from the Overlook Hotel's past are revealed, and the hotel itself attempts to laim the very souls of the Torrence family. A searing study of a family torn apart, and a nightmarish glimpse into the dark recesses of human weakness and dementia.